Internal and external loads in professional women’s Rugby Sevens: analysis of a block-based training session with small games - Filipe Oliveira Bicudo; Lucas Savassi Figueiredo; Lucieli Teresa Cambri; Jacielle Carolina Ferreira; Ana Paula da Silva Azevedo; Gustavo Ferreira Pedrosa; Samuel da Silva Aguiar; Henrique de Oliveira Castro (Human Movement, 2024)
Purpose This study aimed to compare internal load (IL) and external load (EL) variables between blocks of a game-based Rugby Sevens training session.